Foliar Diagnosis, Yield and Quality of Pepper (Piper nigrum L.) in Relation to Nitrogen, Phosphorus and Potassium - Sushama P K (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1982)
Pepper vines of variety, Panniyoor-1, of the NPK fertilizer trial maintained at the Pepper Research Station, Panniyoor, Canncanore District were selected for the collection of tissue samples under the present study during 1979-81. The experiment was laid out in a 33 factorial design in a randomized block design, confounding the effect of NP2K2 totally. In order to standardize the best leaf position for foliar diagnosis, the mature leaves of fruit bearing laterals were numbered from the youngest to the oldest, taking the youngest fully matured leaf as the first and they were collected separately. The most suitable season for the collection of leaf intended for foliar diagnosis was also standardized by drawing samples of first mature leaf at different stages of growth of the vine. The suitability of different types of stem of the plant such a runner shoot, top shoot, fruit bearing lateral and hanging shoot for tissue analysis was also examined. For studying the variations in the oleoresin content of berry as influenced by fertilizer nutrients, the berries were sampled at different stages of maturity. The first mature leaf better reflected variation in the levels of application of nitrogen to the vine. As the phosphorus and potassium contents of the first mature leaf established significant positive correlation with yield of pepper, it is recommended as an index for foliar diagnosis in pepper in relation to nitrogen, phosphorus and potassium status of the vine. The period just prior to flushing is the most suitable season for the collection of leaf samples intended for foliar diagnosis. During this period, the first mature leaf is sensitive to application for different levels of nitrogen and its potassium content established significant positive correlation with yield. For assessing the phosphorus status of the vine, the runner shoot appeared to be a better tissue as its phosphorus content established a high degree of correlation with yield. As compared to other types of stem, the highest content of potassium was found in the fruit bearing laterals. The periods of maturity significantly influenced the phosphorus, potassium and oleoresin contents of the berry. Their contents increased from four to six months after flowering and then decreased. The graded doses of nitrogen, phosphorus and potassium and their interaction failed to influence the percentage of oleoresin content of pepper.